FORTIFIKASI FOSFOR PADA PEMBUATAN PUPUK ORGANIK PADAT BERBAHAN BAKU FESES SAPI POTONG TERHADAP KADAR FOSFOR DAN C/N RASIO - Rahmawati, Mia; Santoso, R. Singgih Sugeng; Setyaningrum, Agustinah (ANGON: Journal of Animal Science and Technology, 2020)
Background. The purpose of this studied was to determine the effect of addied phosphorus to phosphorus level and C/N ratio on the process of solid organic fertilizer decomposition. Materials and Methods. The research material used were fresh beef cattle feces, sawdust, activator, lime dolomite and phosphorus. It were used hoe, scale and a set of laboratory equipment to test P and C/N ratio. The research methodology was an experimental study using a complete random design (RAL) with 3 repeated treatments 6 times. The parameters measured are phosphorus level and C/N ratio of solid organic fertilizer. Results. The results showed that with phosphorus fortification had a very noticeable effect on phosphorus levels (P < 0.01) and a noticeable effect on the C/N ratio level (P < 0.05). Results of the phosphorus level reached 4,08% and C/N ratios of 22,88. Conclusion. The conclusion of the studied was phosphorus fortification can increase P level and reduce C/N ratio of solid organic fertilizer made from beef cattle feces.